2017
DOI: 10.1186/s40463-017-0190-6
|View full text |Cite
|
Sign up to set email alerts
|

Does drug-induced sleep endoscopy change the surgical decision in surgically naïve non-syndromic children with snoring/sleep disordered breathing from the standard adenotonsillectomy? A retrospective cohort study

Abstract: BackgroundAdenotonsillectomy is the most commonly performed operation for pediatric snoring/sleep disordered breathing (S/SDB). However, 20–40% of patients will fail to improve. Drug-induced sleep endoscopy (DISE) may provide a more individualized surgical plan and limit unsuccessful surgeries. The aim of this study was to assess the impact of DISE on surgical decision-making in surgically naïve children with S/SDB.MethodsA retrospective observational cohort study was undertaken at the Stollery Children’s Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 47 publications
3
24
0
2
Order By: Relevance
“…They found a significant improvement in both oAHI and oxygen saturation nadir ( p < 0.001) with the most frequently performed surgeries being adenoidectomy (41%), supraglottoplasty (38%), tonsillectomy (27%), lingual tonsillectomy (13%), nasal surgery (9%), and palatoplasty (5%) . Gazzaz et al recently demonstrated that DISE affects decision‐making in surgically naïve children with snoring and sleep‐disordered breathing in up to 35% of children . This finding is in agreement with Hybaskova et al who found that the surgical plan was changed in 60.8% of patients with obstructive sleep apnea undergoing DISE which often allowed the surgeon to address multiple levels of airway obstruction…”
Section: Discussionsupporting
confidence: 70%
“…They found a significant improvement in both oAHI and oxygen saturation nadir ( p < 0.001) with the most frequently performed surgeries being adenoidectomy (41%), supraglottoplasty (38%), tonsillectomy (27%), lingual tonsillectomy (13%), nasal surgery (9%), and palatoplasty (5%) . Gazzaz et al recently demonstrated that DISE affects decision‐making in surgically naïve children with snoring and sleep‐disordered breathing in up to 35% of children . This finding is in agreement with Hybaskova et al who found that the surgical plan was changed in 60.8% of patients with obstructive sleep apnea undergoing DISE which often allowed the surgeon to address multiple levels of airway obstruction…”
Section: Discussionsupporting
confidence: 70%
“…A total of 1247 patients were included (69.21% males). Children were recruited in three studies [10-12].…”
Section: Resultsmentioning
confidence: 99%
“…In children, two studies revealed the changed sites of airway collapse [10-11]. Tonsillectomy was the most frequently changed procedure, with an 88.3% change rate.…”
Section: Resultsmentioning
confidence: 99%
“…Various body positions and situations such as lateral sleep position, head turning, mandibular pull up, mouth opening, or continuous positive airway pressure (CPAP) titration can be applied [57]. These simulations provide crucial information for decision making [3, 8, 9]. However, the conventional single channel DISE system usually records flexible endoscopic images only.…”
Section: Introductionmentioning
confidence: 99%